Former substance abusing women, interpersonal relationships and social cognition: Social comparison & sober housemate harmony predict women's abstinence-specific efficacy. Issue 2 (3rd April 2022) - Walt, Lisa; Lupei, Madeline; Jason, Leonard A.
Abstract: The Relational Theory of Addiction hypothesizes that women's substance abuse SUD development and (SA) recovery experiences differ from men's because of women's tendency to form nested self-concepts and increased relative desire for close interpersonal connections. We suggest that these two differences may have a dynamic and complex influence on recovery success, particularly for women living in group sober homes. This project uses Relational and Social Cognitive Theories as theoretical springboards to investigate the link between Tendency to Engage in Automatic Negatively Affected Social Comparisons (TEANSAC) and Sober Housemate Harmony (SHH) on women's individual perceptions of Abstinence Specific Self-Efficacy (ASSE) . We administered short surveys to women ( N = 25) that had recently left inpatient SA treatment and were currently living in a group sober home to assess TEANSAC, SHH and ASSE. Results illustrated that higher TEANSAC scores predicted lower ASSE scores. However, SHH did not predict ASSE scores. Finally, an interaction effect was found in which SHH moderated the relationship between TEANSAC and ASSE. Specifically, we found that highly harmonious sober homes may buffer against the negative effects of increased TEANSAC scores. This project suggests that social cognitive and interpersonal variables may be important factors to consider for women's long-term recovery success.